The association between parity and spontaneous preterm birth: a population based study - Bouchra Koullali; Maud D. van Zijl; Brenda M. Kazemier; Martijn A. Oudijk; Ben W. J. Mol; Eva Pajkrt; Anita C. J. Ravelli (BMC, 2020)
Abstract Background Preterm birth is the leading cause of perinatal mortality and neonatal morbidity worldwide. Many factors have been associated with preterm birth, including parity. The aim of the present study was to investigate associations between parity and risk of spontaneous preterm birth. Methods We conducted a retrospective study including live singleton births (≥22 weeks) of women with a first, second, third, fourth or fifth pregnancy in The Netherlands from 2010 through 2014. Our primary outcome was risk of spontaneous preterm birth < 37 weeks. Secondary outcomes were spontaneous preterm birth < 32 and < 28 weeks. Results We studied 802,119 pregnancies, including 30,237 pregnancies that ended spontaneously < 37 weeks. We identified an increased risk for spontaneous preterm birth < 37 weeks in nulliparous women (OR 1.95, 95% CI 1.89-2.00) and women in their fifth pregnancy (OR 1.26, 95% CI 1.13-1.41) compared to women in their second pregnancy. Similar results were seen for spontaneous preterm birth < 32 and < 28 weeks. Conclusion Our data show an independent association between nulliparity and spontaneous preterm birth < 37, < 32 and < 28 weeks. Furthermore, we observed an increased risk for spontaneous preterm birth in women in their fifth pregnancy, with highest risk for preterm birth at early gestational age.